White matter neuro-plasticity in mental arithmetic: Changes in hippocampal connectivity following arithmetic drill training. (May 2019) - Klein, Elise; Willmes, Klaus; Bieck, Silke M.; Bloechle, Johannes; Moeller, Korbinian
Abstract: Verbally-mediated arithmetic fact retrieval has been suggested to be subserved by a left-lateralized network including angular gyrus and hippocampus. However, the contribution of these areas to retrieval of arithmetic facts has been under debate lately, challenging the prominent role of the angular gyrus in arithmetic fact retrieval. In the present study, we evaluated changes in structural connectivity of left hippocampus and left angular gyrus in 32 participants following a short extensive drill training of complex multiplication. We observed a significant increase of structural connectivity in fibers encompassing the left hippocampus but not the left angular gyrus. As such, our findings substantiate that the left hippocampus plays a central role in arithmetic fact retrieval. While both structures, left angular gyrus and left hippocampus seem to be parts of the network processing arithmetic facts, hippocampus actually seems to subserve encoding and retrieval of arithmetic facts. In turn, the role of the left angular gyrus might rather be to mediate the fact retrieval network as to whether or not processes of fact retrieval are referred to.